2021
DOI: 10.1088/2053-1591/abd5d7
|View full text |Cite
|
Sign up to set email alerts
|

Effect on microstructure and corrosion resistance of semi-solid slurry of 7A04 aluminum alloy by electromagnetic stirring

Abstract: The microstructures and corrosion resistance of electromagnetic stirring (EMS) semi-solid slurry and as-cast 7A04 aluminum alloy were compared in this work. The results show that the primary microstructure of the as-cast 7A04 aluminum alloy is mainly dendritic and columnar dendrite with obvious elements segregation. In contrast, semi-solid processing can effectively form homogeneous and round primary α-Al grains, and significantly reducing element segregation. In addition, the main phases of the two forming me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The analysis showed that after applying EMS, the primary phase and the remaining liquid phase had uncoupled motions, which promoted crystal proliferation and refined the solidification structure, revealing the potential of EMS technology. Zhu et al [14] compared the microstructure and corrosion resistance of 7A04 aluminum alloys prepared by as-cast and EMS, and the results showed that uniform and circular primary α-Al grains could be effectively formed under the action of EMS, and element segregation was significantly reduced, thus effectively improving the corrosion resistance of 7A04 aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis showed that after applying EMS, the primary phase and the remaining liquid phase had uncoupled motions, which promoted crystal proliferation and refined the solidification structure, revealing the potential of EMS technology. Zhu et al [14] compared the microstructure and corrosion resistance of 7A04 aluminum alloys prepared by as-cast and EMS, and the results showed that uniform and circular primary α-Al grains could be effectively formed under the action of EMS, and element segregation was significantly reduced, thus effectively improving the corrosion resistance of 7A04 aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of solid phase, the shrinkage produced during the solidification process is small, and it is not easy to produce hole defects [3], so that the semi-solid forming products have high compactness and can be heat treated to improve the mechanical properties again [4,5]. Initially, semi-solid processing techniques, such as mechanical stirring method [5,6] and electromagnetic stirring method [7,8], were mainly used for experimental research with few industrial applications. In recent years, researchers have designed preparation methods with simple equipment and low cost, such as gas induced semi-solid process [9,10], selfinoculation method [11], rapid slurry forming [12,13], cooling ramp method [14], serpentine channel method [15], helical groove method [16], etc., and the formation mechanism of the slurry is also being continuously improved and developed [17,18].…”
Section: Introductionmentioning
confidence: 99%